Identification of biomarkers and potential drug targets for esophageal cancer: a Mendelian randomization study - Chengjun Li; Xiaomeng Cui; Mudan Ren; Yan Yin; Shuixiang He (Scientific Reports)
Abstract Esophageal cancer (EC) is a common and deadly malignancy of the digestive system. Currently, effective treatments for EC are limited and patient prognosis remains poor. In this study, we utilized Mendelian Randomization (MR) to identify potential drug targets for EC by analyzing proteins linked to the disease risk. A total of 734 plasma proteins and 4,479 druggable genes were obtained from recent studies, and two-sample MR analyses were conducted to investigate causal relationships between these proteins and EC. The cis-pQTL data of the proteins was analyzed after filtering. The inverse variance weighted (IVW) method was the primary analytical approach in MR analysis. Steiger filtering, heterogeneity and pleiotropy tests, Summary-data-based Mendelian Randomization (SMR) analysis, and Bayesian co-localization analysis were implemented to consolidate the results further. Moreover, drugs corresponding to the identified proteins were found in the DrugBank database. Five proteins HPSE, ST3GAL1, CEL, KLK13, and GNRH2 were identified as highly associated with EC. HPSE and GNRH2 showed protective effects with odds ratios (OR) of 0.80 (95% confidence interval [CI], 0.70–0.92) and 0.73 (95% CI 0.54–0.98), respectively. In contrast, increased expression of ST3GAL1(OR, 1.37; 95% CI 1.04–1.82), CEL (OR, 1.27; 95% CI 1.08–1.49), and KLK13 (OR, 1.22; 95% CI 1.04–1.42) were all associated with a higher risk of EC. In addition, the HPSE protein showed moderate colocalization with EC [coloc.abf-posterior probability of hypothesis 4 (PPH4) = 0.637]. Furthermore, the sensitivity analyses indicated no heterogeneity or pleiotropy. Therefore, these findings present promising drug targets for EC and deserve further clinical investigation.